On Pappian and Desarguesian affine planes - Pshyk, V. O. (Matematychni Studii, 2025)
We present a complete proof of the classical Heisenberg’s Theorem on the Desarguesian property of Pappian  affine planes. In the proof we consider two cases, one of which was omitted in the original Hessenberg’s proof, making it incomplete.